Experimental analysis of bending performance of secondary steel fibre-reinforced concrete and fuzzy optimisation of damage constitutive model - Xiaoqian, Wang; Xiangyu, Qiu; Yuzhi, Chen; Ling, Song (Frontiers in Materials, 2025)
Four-point bending tests were conducted on SFRC of different varieties, lengths, and dosages to determine their effects on the flexural tensile strength and flexural toughness of secondary mixed concrete. Under the same length and dosage, end-hooked steel fibres had the best reinforcing effect on the flexural tensile strength. The addition of the fibres significantly improved the flexural toughness of the concrete. Except for the shear-type steel fibres, the load–deflection curves of all the specimens were complete and uninterrupted. However, owing to the combined influence of factors such as the type of steel fibre, fibre length, and fibre content, the bending performance exhibited uncertainty. Thus, the uncertain state caused by microdefects in the secondary SFRC material was regarded as the damage variable, and the damage constitutive model of the secondary SFRC under a bending load was obtained by employing the Weibull distribution. An improved fuzzy ant colony optimisation (FACO) algorithm was utilised to conduct fuzzy optimisation of the shape, scale, and position parameters of the damage constitutive model. The numerical example indicated that the constitutive-model value of the bending damage of secondary SFRC optimised by the FACO algorithm was closer to the actual value than the fitting value of the traditional ant colony optimisation (ACO) algorithm and least-squares method. Overall, the error was smaller and the algorithm was more efficient. The results indicate that the proposed model and method are effective for analysing uncertainty problems in large-volume hydraulic structure engineering.